LNG systems for natural gas propelled ships. Issue 1 (November 2015) - Chorowski, M; Duda, P; Polinski, J; Skrzypacz, J
Abstract: In order to reduce the atmospheric pollution generated by ships, the International Marine Organization has established Emission Controlled Areas. In these areas, nitrogen oxides, sulphur oxides and particulates emission is strongly controlled. From the beginning of 2015, the ECA covers waters 200 nautical miles from the coast of the US and Canada, the US Caribbean Sea area, the Baltic Sea, the North Sea and the English Channel. From the beginning of 2020, strong emission restrictions will also be in force outside the ECA. This requires newly constructed ships to be either equipped with exhaust gas cleaning devices or propelled with emission free fuels. In comparison to low sulphur Marine Diesel and Marine Gas Oil, LNG is a competitive fuel, both from a technical and economical point of view. LNG can be stored in vacuum insulated tanks fulfilling the difficult requirements of marine regulations. LNG must be vaporized and pressurized to the pressure which is compatible with the engine requirements (usually a few bar). The boil-off must be controlled to avoid the occasional gas release to the atmosphere. This paper presents an LNG system designed and commissioned for a Baltic Sea ferry. The specific technical features and exploitation parameters of the system will be presented. The impact of strict marine regulations on the system's thermo-mechanical construction and its performance will be discussed. The review of possible flow-schemes of LNG marine systems will be presented with respect to the system's cost, maintenance, and reliability.